“Ontological mislocations”, modos de conciencia e historia. Indiscernibles, desplazamiento y horizontes de posibilidad en la filosofía de Arthur Danto - Lavagnino, Nicolás (2013)
“'Ontological Mislocations', Modes of Conciousness and History: Indiscernibles, Displacement and Horizons of Possibility in the Philosophy of Arthur Danto”. In this article my purpose is to trace the links between three key elements in Arthur Danto’s philosophy: first, the capital consideration, for philosophical purposes, of human beings as ens representans, departing from the elucidation of a type of cognitive episode that Danto called “basic”. Secondly,I am concerned with the recurring appeal to a plane of consciousness that supports a dual characterization in terms of the pair inside/outside and enables alogical space that is characteristic of philosophy as a reflective mode. Finally, I will treat a form of cognitive failure that Danto considered fundamental to the philosophical perspective, which leads to a specific type of restructuring of our ordinary system of beliefs. What I contend is that in Danto’s philosophical system these three elements become intelligible from the postulation of an effectual background that the author calls “objective historical structure”, which is characterized in terms of the horizons of possibility and impossibility that it delineates. These figures of historical-temporal possibility and impossibility constitute the matrix of historicity itself and also contribute decisively to shaping the permanent nucleus of dantean philosophical concerns.